EXTH-01. SECOND GENERATION OF INDUCED NEURAL STEM CELLS TO MIGRATE AND KILL AS AN ADJUVANT TO RADIOTHERAPY IN NON-SMALL CELL LUNG CANCER METASTASIS. (12th November 2021) - Mercer-Smith, Alison; Thang, Morrent; Buckley, Andrew; Valdivia, Alain; Jiang, Wulin; Bell, Noah; Kumar, Rashmi; Bomba, Hunter; Woodell, Alex; Luo, Daniel; Floyd, Scott; Hingtgen, Shawn
Abstract: Non-small cell lung cancer (NSCLC) spread to the leptomeninges is devastating with a median survival of only a few months. Radiation is frequently offered for symptomatic relief but alone does not eliminate leptomeningeal metastases (LMM). With no standard-of-care for patients with LMM, new adjuvant therapies are desperately needed in order to combat this disease. Neural stem cells (NSCs) have shown remarkable promise as drug delivery vehicles in the treatment of brain tumors due to their inherent tumoritropic properties. Using a cell sphere culture-based system, we have transdifferentiated fibroblasts into a second-generation induced neural stem cell (hiNeuroS) secreting the cytotoxic protein tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) to allow for the possibility of readily available, autologous cell carriers. Herein, we provide evidence that hiNeuroS-TRAIL cells can migrate to and suppress growth of NSCLC metastases in combination with radiation. In vitro time-lapse motional analysis and in vivo post-mortem tissue analysis showed that hiNeuroS-TRAIL cells migrate to NSCLC tumors. In vitro co-cultures with isobologram analysis suggests that TRAIL and radiation together have a synergistic cytotoxic effect on NSCLC tumors. In an intratumoral injection model of hiNeuroS-TRAIL, mice treated with the combination therapy of hiNeuroS-TRAIL and 2 Gy together had a small fraction of the mean tumor volume (6.4%) of controls (100%) compared to monotherapies (107.3% radiation-only, 46.6% hiNeuroS-TRAIL only). Only combination-treated mice demonstrated a significant extension in survival, which amounted to a 42% extension compared to controls. In the LMM model with ICV-infused therapy, the combination-treated mice showed significantly smaller tumor volumes (2.0%) compared to control (100%) or 2 Gy (54.9%) treated mice. Mice treated with hiNeuroS-TRAIL-only also showed only 4.6% of the tumor volume of control mice. Combination-treated mice and hiNeuroS-TRAIL-treated mice both showed significant improvements in survival (36.6% and 46.3% median extension in survival, respectively compared to controls).